Minimal change chronic pancreatitis. Issue 11 (November 1992) - Walsh, T N; Rode, J; Theis, B A; Russell, R C
Abstract : In patients with severe abdominal pain, of pancreatic origin, there are a few with minimal or equivocal findings on pancreatic investigation and in whom the aetiology of their pancreatic disease is elusive. The findings and outcome in 16 of these patients (four men and 12 women) who underwent resection are reported. Pancreatic imaging showed minimal or equivocal findings in all 16; pancreas divisum was present in five. All were managed conservatively at first but resection was required for progression of symptoms. A drainage procedure was performed initially in five patients but relief of pain was at best transitory before further surgery was required. Partial resection was needed in 12, of whom eight required subsequent completion pancreatectomy and four had a one stage total resection. Nine patients are currently pain free after resection or are very much improved, while six are no better and one patient has died from an unrelated cause. Histology of resected specimens showed chronic inflammatory changes accompanied by subtle non-inflammatory changes in all but one. These changes include duct proliferation, duct complex formation, adenomatous nodules, and acinar cell atrophy, the significance of which is unclear. These findings suggest a syndrome of minimal macroscopic and radiological change chronic pancreatitis with pain as its chief clinical feature and a distinct histology, the aetiology of which is unclear. It seems that there is a distinct syndrome of minimal change pancreatitis, among the group of patients which presents with the clinical features of chronic pancreatitis.